Innovation in Pesantren Development as a Perspective Study of the Quality Development of Pesantren in the Era of Disruption 4.0 - Muadin, Akhmad; Ilyasin, Mukhamad; Saleah, Prasart (SYAMIL: Journal of Islamic Education, 2023)
Islamic boarding schools are faced with a situation of rapid change (disruption era 4.0), this has resulted in significant changes in various aspects of life, including Islamic education and Islamic boarding schools. These changes require Islamic boarding schools to innovate in order to improve the quality of their education. Innovation in developing the quality of Islamic boarding school education is important in order to face challenges in the era of disruption 4.0. This research uses a qualitative approach, data mining is carried out through observation, interviews and documentation, while data analysis uses interactive data analysis. The research results show that innovation in developing the quality of Islamic boarding school education can have a positive influence on various aspects, such as the quality of Islamic boarding school graduates, the competitiveness of Islamic boarding schools, and public trust in Islamic boarding schools. Innovation is carried out in certain fundamental aspects, namely; curriculum innovation, learning method innovation, facilities and infrastructure innovation as well as managerial innovation. This innovation is an effort to improve the quality of Islamic boarding school education so that it can answer the challenges in the era of disruption 4.0.